2016
DOI: 10.1111/ecin.12415
|View full text |Cite
|
Sign up to set email alerts
|

The Payoff to Consistency in Performance

Abstract: This study investigates whether firms are willing to pay higher wages to workers who demonstrate consistent performance than to those whose performance is more volatile. A formal model reflects a production technology view, assuming the law of diminishing marginal product. This model suggests that a more consistent worker produces higher expected output and therefore receives a higher wage. The test of the model uses data from the National Basketball Association. The empirical data support the model: Players w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 79 publications
4
15
0
Order By: Relevance
“…Using the smallest standard deviation from the mean is one way to measure consistency (Depken et al , 2017). Previous work performance can be an accurate indicator of future work performance but often goes unobserved (Deutscher et al , 2017). In addition, Deutscher et al (2017) further suggested that the expectation of output lessens with inconsistency and can affect worker compensation.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the smallest standard deviation from the mean is one way to measure consistency (Depken et al , 2017). Previous work performance can be an accurate indicator of future work performance but often goes unobserved (Deutscher et al , 2017). In addition, Deutscher et al (2017) further suggested that the expectation of output lessens with inconsistency and can affect worker compensation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous work performance can be an accurate indicator of future work performance but often goes unobserved (Deutscher et al , 2017). In addition, Deutscher et al (2017) further suggested that the expectation of output lessens with inconsistency and can affect worker compensation. Performance consistency from workers provides managers projections toward outcomes from which managers can develop competitive strategies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In some cases, principals prefer consistent performances to volatile ones by their agents (Bodvarsson & Brastow, 1998;Deutscher, Gürtler, Prinz, & Weimar, 2017;Dickinson & Oaxaca, 2014), in other cases, researchers suggest that principals prefer inconsistent agents to consistent ones (Bollinger & Hotchkiss, 2003;Deutscher & Büschemann, 2016). Although existing literature finds evidence for either case, the question under which conditions inconsistency is penalized or rewarded remains ambiguous, especially because the necessary conditions are not identified.…”
Section: Introductionmentioning
confidence: 99%
“…Bollinger and Hotchkiss (2003) empirically test baseball player's salaries and performances and find that inconsistent baseball players earn a salary premium compared to their colleagues who have the same average performance but do not offer larger upside potential. Deutscher and Büschemann (2016) and Deutscher et al (2017) study the relationship between player salaries and performance variation in the German Bundesliga and in the NBA, respectively. For German football, the researchers offer evidence that players are more highly rewarded for more inconsistent performance.…”
Section: Introductionmentioning
confidence: 99%
“…Deutscher and Büschemann (2014a) find strong evidence that professional soccer players in Germany who perform inconsistently receive a salary premium. However, they find that consistency is rewarded in NBA player contracts (Deutscher & Büschemann, 2014b). Different performance incentives and different athletic endeavors may elicit the various findings about the value of consistency.…”
Section: Introductionmentioning
confidence: 99%